CO2 electrochemical reduction method based on tip enhanced electric field
Nano-triangular gold catalysts in a strong electric field enhance CO2 electrochemical reduction efficiency by polarizing and activating CO2 molecules, addressing the limitations of existing catalysts and reducing energy consumption and environmental impact.
Patent Information
- Application Number
- CN202411814351.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
AI Technical Summary
Current methods for CO2 electrochemical reduction face challenges in efficiently activating and polarizing CO2 molecules due to their non-polar structure, leading to low reaction efficiency and high energy consumption, with existing catalysts like metal nanoparticles and alkali metal ions causing electrode fouling and environmental concerns.
The use of nano-triangular gold catalysts (AuNTs) in an electrochemical cell with a strong electric field to polarize and activate CO2 molecules, reducing the reaction energy barrier and enhancing their adsorption and reduction efficiency without the need for alkali metal ions.
The nano-triangular gold catalysts significantly improve CO2 reduction efficiency by increasing the polarization of CO2 molecules, achieving higher current densities and stability at lower potentials, while avoiding electrode fouling and environmental pollution.
Smart Images

Figure CN119685855A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical reduction, and in particular to a CO2 electrochemical reduction method based on a tip-enhanced electric field. Background Art
[0002] Electrochemical reduction of CO2 (CO2R) is an important technology that can convert CO2 into valuable chemicals and fuels. This technology has broad application prospects in environmental protection and energy utilization. However, due to the highly stable non-polar structure of CO2 molecules, it is difficult to adsorb and activate them on the electrode surface, which makes the kinetic efficiency of the CO2 reduction reaction low. Therefore, how to improve the adsorption and activation efficiency of CO2 is the main challenge of the electrochemical reduction of CO2.
[0003] At present, methods to improve the adsorption and activation efficiency of CO2 include using metal nanoparticles as catalysts and introducing alkaline metal cations (such as K + ). Among them, the introduction of alkaline metal cations (such as K + ) can promote the adsorption and activation of CO2 and improve the kinetic performance of its reduction reaction. However, this method has obvious disadvantages: on the one hand, alkaline metal cations are easy to form carbonate precipitation in the electrolyte, resulting in electrolyte pollution and electrode clogging, increasing the maintenance difficulty and operating cost of the system; on the other hand, the adverse effects of alkaline electrolytes on the environment also limit the extensiveness of its practical application. It can be seen that the existing methods for improving the adsorption and activation efficiency of CO2 have the problems of low polarization and activation efficiency of CO2 molecules and high operating environment and operating cost. As for metal nanoparticles as catalysts, they can enhance the reduction reaction of CO2 by providing higher surface area and reaction active sites. Gold (Au)-based catalysts have become a research hotspot for CO2 electrochemical reduction due to their excellent chemical stability and CO2 reduction selectivity. However, traditional metal nanoparticles (such as AuNPs and AuCPs) are usually spherical or obtuse structures. These structures cannot generate sufficiently strong local electric fields during the reaction, resulting in limited polarization and activation effects of CO2 molecules. Specifically, the surface electric field of these obtuse or spherical nanoparticles is weak and cannot effectively break the non-polar structure of CO2 molecules, resulting in low reaction efficiency and high energy consumption.
[0004] At present, although existing studies have shown that electric fields can enhance the enrichment and adsorption of alkali metal ions, thereby indirectly affecting the adsorption and reaction behavior of CO2 molecules, there is no technology that can fully utilize the enhanced local electric field to directly improve the adsorption and activation efficiency of non-polar molecules. Especially for CO2 molecules, their non-polar structure makes it difficult to achieve effective polarization by traditional methods. Therefore, it is very necessary to significantly improve the adsorption and activation efficiency of CO2 molecules by enhancing the electric field to overcome the limitations of its non-polar structure and reduce the reaction energy barrier. This technology will provide a new solution for CO2 electrochemical reduction and open up new directions for the research of non-polar molecular reaction systems. Summary of the invention
[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a method for electrochemical reduction of CO2 based on a tip-enhanced electric field. The present invention prepares a nano-triangular gold catalyst AuNTs, which is a nano-triangular gold catalyst with a tip structure. The nano-triangular gold catalyst AuNTs is used as an electrode to construct an electrolytic cell system. When the electrolytic cell system is used for electrochemical reduction of CO2, CO2 gas is introduced and the electric field strength on the catalyst surface is adjusted to 1.0×10 8 -1.2×10 8 V / m treatment for 10-30 min causes the CO2 molecules to be polarized, changing their electron distribution state, thereby reducing their reaction energy barriers. As a result, the polarized CO2 molecules are further activated under the action of the electric field, and can more easily participate in the reduction reaction to generate the target product.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for electrochemical reduction of CO2 based on a tip-enhanced electric field, comprising the following steps:
[0008] The working electrode was prepared using nano-triangular gold catalysts, and sulfuric acid was used as the electrolyte solution to construct an electrolytic cell system for electrochemical reduction of CO2.
[0009] The nano-triangular gold catalyst is prepared by the following method:
[0010] (1) mixing a hexadecyltrimethylammonium bromide solution, a KI solution and a gold chloride solution to obtain a mixed solution; adding a NaOH solution and an ascorbic acid solution to the mixed solution in sequence, and waiting for the solution to become colorless to obtain a precursor solution;
[0011] (2) adding NaOH solution to the precursor solution until the solution turns blue to obtain a nano-triangular gold catalyst dispersion;
[0012] (3) adding hexadecyltrimethylammonium bromide solution to the nano-triangular gold catalyst dispersion, mixing and then standing, purifying and centrifuging, collecting the precipitate after centrifugation, and obtaining the nano-triangular gold catalyst.
[0013] Preferably, when the electrolytic cell system is used for electrochemical reduction of CO2, CO2 gas is introduced and the electric field strength of the electrolytic cell system is adjusted to 1.0×10 8 -1.2×10 8 V / m treatment for 10-30 min, and then electrochemical reduction of CO2 was carried out at a potential of -0.7V to -1.1V.
[0014] The nano-triangular gold catalyst used in the present invention has a pointed structure and is placed in an electric field with an intensity of 1.0×10 8 -1.2×10 8 V / m strong electric field will enhance the local electric field effect, and the electrolyte solution used in the present invention is sulfuric acid, and the electrolyte composition does not contain alkali metal cations. Therefore, the present invention can fully utilize the enhanced local electric field to directly improve the adsorption and activation efficiency of non-polar molecules. Under the action of this sharp enhanced electric field, the CO2 molecule can generate a dipole moment of 1.25D, and the C=O bond length in the CO2 molecule can be increased from Increase to Further reducing the C=O bond energy makes CO2 adsorption and activation more effective.
[0015] Preferably, the purity of CO2 gas is 99.999% and the flow rate is 15-25cm 3 / min.
[0016] Preferably, in the electrochemical reduction of CO2, the reaction temperature is 20-28°C and the reaction time is 100h.
[0017] Preferably, the concentration of the sulfuric acid is 0.07-0.1M.
[0018] Preferably, in step (1), the cetyltrimethylammonium bromide solution is prepared by mixing 0.1 mol / L cetyltrimethylammonium bromide stock solution and water in a volume ratio of (1.5-1.8):8.
[0019] Preferably, in step (1), the volume ratio of the hexadecyltrimethylammonium bromide solution, the KI solution and the gold chloride solution is (9.5-9.8) mL: (70-80) μL: 80 μL.
[0020] Preferably, in step (1), the concentration of the KI solution is 0.01 M, the gold chloride solution is a mixture of HAuCl4·3H2O and water, the concentration of the gold chloride solution is 25.4 mM, the concentration of the NaOH solution is 0.1 M, and the concentration of the ascorbic acid solution is 0.064 M.
[0021] Preferably, in step (1), the volume ratio of the gold chloride solution, the NaOH solution and the ascorbic acid solution is 80:(20-21):80.
[0022] Preferably, in step (2), the volume ratio of the precursor solution to the NaOH solution is (3-5):1; and the concentration of the NaOH solution is 0.1M.
[0023] Preferably, in step (3), the volume ratio of the nano-triangular gold catalyst dispersion to the hexadecyltrimethylammonium bromide solution is 1:1.
[0024] Preferably, in step (3), the concentration of the hexadecyltrimethylammonium bromide solution is 0.2M.
[0025] Preferably, in step (3), the standing time is 24-40 hours.
[0026] Preferably, in step (3), the purification treatment is: repeatedly centrifuging and resuspending the suspension after standing to remove impurities with irregular morphology and substances that do not participate in the reaction.
[0027] Preferably, the specific operation of preparing the working electrode using the nano-triangular gold catalyst rich in tip structure is:
[0028] (a) dispersing a nano-triangular gold catalyst rich in tip structures into a hexadecyltrimethylammonium bromide solution to obtain a nano-triangular gold catalyst solution; then adding a Nafion solution and isopropanol to the nano-triangular gold catalyst solution, and stirring to obtain a catalyst ink;
[0029] (b) Spraying the catalyst ink onto the surface of the electrode substrate and drying it to obtain a working electrode.
[0030] Further preferably, in step (a), the solid-liquid ratio of the nano-triangular gold catalyst and the hexadecyltrimethylammonium bromide solution is (400-410) μg:500 μL; and the concentration of the hexadecyltrimethylammonium bromide solution is 40 mM.
[0031] Further preferably, in step (a), the volume ratio of the nanotriangular gold catalyst solution, the Nafion solution and the isopropanol is (1.5-2.5) mL:80 μL:3 mL; and the concentration of the Nafion solution is 5 wt %.
[0032] Further preferably, in step (a), the stirring time is 15-25 min.
[0033] Further preferably, in step (b), the electrode substrate is a gas diffusion electrode (GDE) or carbon paper.
[0034] Further preferably, in step (b), the loading amount of the catalyst ink on the electrode substrate is 0.4-0.6 mg / cm 2 .
[0035] Further preferably, in step (b), the drying treatment is: the electrode substrate sprayed with the catalyst ink is first dried at room temperature for 25-35 minutes, and then dried at 45-55° C. for 1 hour.
[0036] Beneficial effects of the present invention:
[0037] The present invention produces a nano-triangular gold catalyst AuNTs, which is a gold nanocatalyst with a pointed structure. The local electric field enhancement effect under a strong electric field can effectively improve the polarization and activation of CO2 molecules. Compared with the existing commonly used blunt-angle nanocatalysts and commercial gold-carbon catalysts, the nano-triangular catalyst produced by the present invention can achieve higher CO2 polarization at a lower potential, making CO2 molecules easier to be adsorbed and activated, thereby improving the electrochemical reduction efficiency of CO2. At the same time, it also reduces the consumption of electrical energy and achieves the purpose of energy saving and consumption reduction. Specifically, at a potential of -1.0V vs RHE, the CO generation current density of the nano-triangular gold catalyst produced by the present invention is as high as 122mA / cm 2 The CO generation current density of the commonly used blunt-angle nanocatalyst and commercial gold-carbon catalyst is only 29.6 mA / cm 2 and 14.6mA / cm 2 It can be seen that the nano-triangular gold catalyst prepared by the present invention has significant advantages in improving the activity of CO2 reduction reaction.
[0038] The AuNTs catalyst of the present invention exhibits excellent stability in a strong acid electrolyte, and can maintain a stable current density and selectivity during an electrolysis process of up to 100 hours, indicating that the catalyst has good durability and stability in practical applications. In addition, the AuNTs catalyst prepared by the present invention works in a strong acid electrolyte without metal cations, avoiding the formation of carbonates in traditional alkaline media, reducing the risk of environmental pollution, and having better environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1: Electron microscope images of the nano-triangle gold catalyst with a tip structure obtained in Example 1; wherein a is an electron microscope image of the nano-triangle gold catalyst at 200 nm; b is an electron microscope image of the nano-triangle gold catalyst at 30 nm; c is an electron microscope image of the nano-triangle gold catalyst at 2 nm;
[0040] Figure 2 : Gas chromatogram of the nano-triangular gold catalyst with a tip structure obtained in Example 1;
[0041] Figure 3 : Nuclear magnetic resonance image of the nano-triangular gold catalyst with a tip structure obtained in Example 1;
[0042] Figure 4 : Comparison of electric field distribution of nano-gold catalysts of different morphologies; wherein A is the electric field distribution of the nano-triangular gold catalyst prepared in Example 1; B is the electric field distribution of the obtuse-angle nano-gold catalyst prepared in Comparative Example 1; C is the electric field distribution of the commercial gold-carbon catalyst;
[0043] Figure 5 : The effective current density, Faraday efficiency and cathode energy efficiency of nano-gold catalysts with different morphologies in Experimental Example 1 are plotted as a function of potential; wherein A is a plot of effective current density as a function of potential; b is a plot of Faraday efficiency as a function of potential; and c is a plot of cathode energy efficiency as a function of potential;
[0044] Figure 6 : The total current density and Faraday efficiency of the nano-triangular gold catalyst in Experimental Example 3 change over time;
[0045] Figure 7 : The graph of the dipole moment of CO2 molecule changing with the tip electric field strength, where A is the dipole moment change graph and B is the electrostatic potential change graph. DETAILED DESCRIPTION
[0046] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0047] In the prior art, in the electrochemical reduction of CO2, metal nanoparticles are often used as catalysts or alkaline metal cations (such as K + ) to improve the adsorption and activation efficiency of CO2. However, the existing metal nanoparticle structure cannot provide a sufficiently strong local electric field, and the polarization and activation efficiency of CO2 molecules are still low; although the introduction of alkali metal cations can enhance CO2 reduction, it is easy to cause electrolyte pollution and system blockage, increase maintenance difficulty and operating costs, and bring potential negative impacts to the environment.
[0048] Based on this, the present invention provides a nano-triangular gold catalyst AuNTs, which has a high-curvature tip structure and can significantly enhance the local electric field under a strong electric field. The formation of the local electric field promotes the CO2 molecules to generate a significant dipole moment, thereby reducing the reaction energy barrier and improving the reaction efficiency.
[0049] Among them, in the present invention, ascorbic acid is selected as a reducing agent to adjust the reduction rate of gold ions to ensure the formation of a triangular morphology; the reaction temperature determines the nucleation rate of the metal nucleus and the diffusion rate in the subsequent growth process. Higher temperatures usually promote anisotropic growth, thereby forming non-spherical particles such as triangles. The present invention controls the reaction temperature to 25°C, which can promote the preferential growth of specific crystal faces. The adsorption behavior of the stabilizer can selectively stabilize specific crystal faces and inhibit the growth of other crystal faces, thereby forming nanoparticles with specific morphology. The present invention selects hexadecyltrimethylammonium bromide as a stabilizer, which selectively adsorbs on the {111} crystal face, inhibits the growth of other crystal faces, and thus forms triangular particles. The length of the reaction time determines the degree of crystal growth. Properly extending the reaction time can enhance the preferential growth of anisotropic crystal faces and ultimately form triangular particles. The present invention ensures that the nucleus grows fully without excessive aggregation or dissolution by optimizing the reaction time. The pH value of the solution affects the coordination state and reduction kinetics of the gold ions, thereby affecting the formation of the morphology. By adjusting the acidity and alkalinity of the solution, precise control of crystal growth can be achieved. Generally speaking, weak acid or neutral conditions are more conducive to the formation of triangular morphology. In summary, the triangular morphology of gold nanoparticles is determined by the comprehensive regulation of reaction conditions, especially the type and concentration of reducing agent, the choice of stabilizer, reaction temperature and time, etc. These parameters affect the nucleation and growth dynamics of gold crystals, and ultimately achieve precise regulation of the triangular morphology.
[0050] At the same time, the present invention also provides a method for electrochemical reduction of CO2 based on a tip-enhanced electric field, specifically, using an AuNTs catalyst with a tip structure as an electrode to construct an electrolytic cell system, when it is used in the electrochemical reduction of CO2, first introduce CO2 gas, and adjust the electric field strength of the system so that the AuNTs catalyst with a tip structure is located in a strong electric field environment, thereby forming a tip electric field, and the formation of the tip electric field will enhance the local electric field effect, and this local electric field effect will increase the dipole moment of the CO2 molecules in the system and increase the C=O bond length, thereby converting the non-polar CO2 molecules into polar molecules, and the polar CO2 molecules will be beneficial to the adsorption and activation of CO2 in the subsequent reaction process, and the activation ability of the CO2 molecules enables the CO2 reduction reaction to be carried out at a lower potential, thereby improving the overall energy efficiency, reducing the power consumption, and achieving the goal of energy saving and consumption reduction. The electrolyte selected by the present invention is sulfuric acid, which does not contain alkali metal cations, and thus, the tip electric field effect of the present invention can be fully applied to change the polarity of the CO2 molecules.
[0051] Specifically, the present invention introduces a tip electric field in the reaction environment by designing a nanocatalyst AuNTs with a high curvature tip structure, forming a high-intensity electric field in a local area, and polarizing the CO2 molecules through the strong action of the tip electric field, changing their electron distribution state, thereby reducing their reaction energy barrier. The polarized CO2 molecules are further activated under the action of the electric field, and can more easily participate in the reduction reaction to generate the target product.
[0052] like Figure 4 As described above, compared with spherical and obtuse nano-gold catalysts, the tip structure of the nano-triangular gold catalyst prepared by the present invention generates a higher local electric field at the tip, which is conducive to enhancing the polarization ability of CO2 molecules. Figure 7 As shown in the figure, the change trend of the polarization degree (dipole moment) of CO2 molecules with the increase of the tip electric field strength. The figure shows that the enhancement of the tip electric field significantly improves the polarization effect of CO2 and increases the dipole moment.
[0053] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0054] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.
[0055] Example 1: Preparation of nano-triangular gold catalyst with pointed structure
[0056] (1) mixing 1.6 mL of 0.1 M hexadecyltrimethylammonium bromide stock solution and 8 mL of ultrapure water to obtain a hexadecyltrimethylammonium bromide solution;
[0057] 9.6 mL of the above-mentioned hexadecyltrimethylammonium bromide solution, 75 μL of 0.01 M KI solution and 80 μL of 25.4 mM gold chloride solution were mixed to obtain a mixed solution, wherein the gold chloride solution was a mixture of HAuCl4·3H2O and water;
[0058] 20.3 μL of 0.1 M NaOH solution was added to the mixed solution to make the solution light yellow, and 80 μL of 0.064 M ascorbic acid solution was added while stirring. The solution gradually turned colorless. At this time, Au(III) was reduced to Au(I) to obtain a precursor solution. The stirring speed was 700 rpm.
[0059] (2) quickly adding 10 μL of 0.1 M NaOH solution to 40 μL of the above precursor solution and shaking vigorously for 1-2 seconds, the color of the solution changes from purple-red to blue. At this time, nano-triangular gold particles (AuNTs) are formed to obtain a nano-triangular gold catalyst dispersion;
[0060] (3) Add an equal amount of 0.2 M hexadecyltrimethylammonium bromide solution to the above nano-triangular gold catalyst dispersion, let it stand for 30 hours to allow the nano-triangular gold particles to further self-assemble, repeat centrifugation and resuspension twice for purification to remove impurities such as irregular morphology and unreacted products, centrifuge, and collect the precipitate after centrifugation, which is the nano-triangular gold catalyst with a pointed structure.
[0061] The nano-triangular gold catalyst (AuNTs) prepared in this example was subjected to a CO2 electroreduction reaction test, and the reaction product was subjected to electron microscopy analysis, gas chromatography analysis, and nuclear magnetic resonance analysis. The results are as follows: Figure 1-Figure 3 shown.
[0062] Depend on Figure 1 It can be seen that the nano-gold catalyst prepared by the present invention has a triangular morphology and a pointed structure. Figure 2 It can be seen that a significant peak is observed at about 4 minutes. The presence of this peak indicates that the main gas phase product of the catalytic reaction is carbon monoxide (CO). No obvious peak signal appears in other time periods, indicating that the catalyst has high selectivity for CO2 reduction reaction and less by-products. Therefore, the nano-triangular gold catalyst with a pointed structure prepared by the present invention has a highly efficient catalytic effect on the conversion of CO2→CO and has good selectivity. Figure 3It can be seen that the characteristic peak of DMSO solvent was observed at 2.5ppm. The signal of H2O was observed at 3.3ppm. No other obvious characteristic peaks of impurities or by-products were observed, which shows that the reaction process produces fewer liquid by-products and no complex liquid by-products are generated in the electrocatalytic reaction, which may be beneficial to improve the subsequent separation and purification efficiency.
[0063] Example 2: Preparation of nano-triangular gold catalyst with pointed structure
[0064] (1) Mixing 1.5 mL of 0.1 M hexadecyltrimethylammonium bromide stock solution and 8 mL of ultrapure water to obtain a hexadecyltrimethylammonium bromide solution;
[0065] 9.5 mL of the above-mentioned hexadecyltrimethylammonium bromide solution, 70 μL of 0.01 M KI solution and 80 μL of 25.4 mM gold chloride solution were mixed to obtain a mixed solution, wherein the gold chloride solution was a mixture of HAuCl4·3H2O and water;
[0066] 20 μL of 0.1 M NaOH solution was added to the mixed solution to make the solution light yellow, and 80 μL of 0.064 M ascorbic acid solution was added while stirring. The solution gradually turned colorless. At this time, Au(III) was reduced to Au(I) to obtain a precursor solution. The stirring speed was 700 rpm.
[0067] (2) quickly adding 10 μL of 0.1 M NaOH solution to 30 μL of the above precursor solution and shaking vigorously for 1-2 seconds, the color of the solution changes from purple-red to blue. At this time, nano-triangular gold particles (AuNTs) are formed to obtain a nano-triangular gold catalyst dispersion;
[0068] (3) Add an equal amount of 0.2 M hexadecyltrimethylammonium bromide solution to the above nano-triangular gold catalyst dispersion, let it stand for 24 hours to allow the nano-triangular gold particles to further self-assemble, repeat centrifugation and resuspension twice for purification to remove impurities such as irregular morphology and unreacted products, centrifuge, and collect the precipitate after centrifugation, which is the nano-triangular gold catalyst with a pointed structure.
[0069] Example 3: Preparation of nano-triangular gold catalyst with pointed structure
[0070] (1) mixing 1.8 mL of 0.1 M hexadecyltrimethylammonium bromide stock solution and 8 mL of ultrapure water to obtain a hexadecyltrimethylammonium bromide solution;
[0071] 9.8 mL of the above-mentioned hexadecyltrimethylammonium bromide solution, 80 μL of 0.01 M KI solution and 80 μL of 25.4 mM gold chloride solution were mixed to obtain a mixed solution, wherein the gold chloride solution was a mixture of HAuCl4·3H2O and water;
[0072] 21 μL of 0.1 M NaOH solution was added to the mixed solution to make the solution light yellow, and 80 μL of 0.064 M ascorbic acid solution was added while stirring. The solution gradually turned colorless. At this time, Au(III) was reduced to Au(I) to obtain a precursor solution. The stirring speed was 700 rpm.
[0073] (2) quickly adding 10 μL of 0.1 M NaOH solution to 50 μL of the above precursor solution and shaking vigorously for 1-2 seconds, the color of the solution changes from purple-red to blue. At this time, nano-triangular gold particles (AuNTs) are formed to obtain a nano-triangular gold catalyst dispersion;
[0074] (3) Add an equal amount of 0.2 M hexadecyltrimethylammonium bromide solution to the above nano-triangular gold catalyst dispersion, let it stand for 40 hours to allow the nano-triangular gold particles to further self-assemble, repeat centrifugation and resuspension twice for purification to remove impurities such as irregular morphology and unreacted products, centrifuge, and collect the precipitate after centrifugation, which is the nano-triangular gold catalyst with a pointed structure.
[0075] Example 4: A method for electrochemical reduction of CO2 based on tip-enhanced electric field
[0076] A working electrode was prepared using a nano-triangular gold catalyst (AuNTs) rich in tip structures, Pt was used as a counter electrode, Ag / AgCl was used as a reference electrode, and 0.07M sulfuric acid was used as an electrolyte solution, which was loaded into a gas flow electrolytic cell to construct an electrolytic cell system for electrochemical reduction of CO2;
[0077] The specific preparation steps of the working electrode are:
[0078] (a) 406 μg of a nano-triangular gold catalyst (AuNTs) rich in tip structures was dispersed in 500 μL of a hexadecyltrimethylammonium bromide solution to obtain a nano-triangular gold catalyst solution; 80 μL of a 5 wt % Nafion solution was added to 2 mL of the nano-triangular gold catalyst solution as a binder to improve the adhesion of the catalyst on the electrode surface, and 3 mL of isopropanol was added to promote dispersion uniformity, and ultrasonic stirring was performed for 20 min to obtain a catalyst ink;
[0079] (b) A 10 cm × 10 cm gas diffusion electrode (GDE) was selected as the electrode substrate, and it was washed alternately with deionized water and isopropanol three times, and then dried at 60 °C for use;
[0080] Use a sprayer to spray the catalyst ink onto the surface of the electrode substrate. The spray volume is 10 μL each time. After evenly distributing the coating, dry it. Repeat the spraying 3–5 times until the loading amount of the catalyst ink on the electrode substrate reaches 0.5 mg / cm 2 The coated electrode was then placed at room temperature to dry naturally for 30 minutes, and then placed at 50°C to dry for 1 hour to ensure that the solvent was completely volatilized and the catalyst was firmly attached to the electrode surface to obtain a working electrode.
[0081] When the electrolytic cell is used for electrochemical reduction of CO2, CO2 gas is introduced and the electric field strength of the electrolytic cell system is adjusted to 1.2×10 8 V / m for 30 min, and then electrochemically reduce CO2 at a potential of -1.0 V. The purity of CO2 gas is 99.999% and the flow rate is 20 cm 3 / min; in the electrochemical reduction of CO2, the reaction temperature is 25℃ and the reaction time is 100h.
[0082] Example 5: A method for electrochemical reduction of CO2 based on tip-enhanced electric field
[0083] A working electrode was prepared using a nano-triangular gold catalyst (AuNTs) rich in tip structures, Pt was used as a counter electrode, Ag / AgCl was used as a reference electrode, and 0.07M sulfuric acid was used as an electrolyte solution, which was loaded into a gas flow electrolytic cell to construct an electrolytic cell system for electrochemical reduction of CO2;
[0084] The specific preparation steps of the working electrode are:
[0085] (a) 400 μg of a nano-triangular gold catalyst (AuNTs) rich in tip structures was dispersed in 500 μL of a hexadecyltrimethylammonium bromide solution to obtain a nano-triangular gold catalyst solution; 80 μL of a 5 wt % Nafion solution was added to 1.5 mL of the nano-triangular gold catalyst solution as a binder to improve the adhesion of the catalyst on the electrode surface, and 3 mL of isopropanol was added to promote dispersion uniformity, and ultrasonic stirring was performed for 15 min to obtain a catalyst ink;
[0086] (b) A 10 cm × 10 cm gas diffusion electrode (GDE) was selected as the electrode substrate, which was washed alternately with deionized water and isopropanol three times, and then dried at 60 °C for later use;
[0087] Use a sprayer to spray the catalyst ink onto the surface of the electrode substrate. The spray volume is 8 μL each time. After evenly distributing the coating, dry it. Repeat the spraying 3–5 times until the loading amount of the catalyst ink on the electrode substrate reaches 0.4 mg / cm 2 The coated electrode was then placed at room temperature to dry naturally for 25 minutes, and then placed at 45°C to dry for 1 hour to ensure that the solvent was completely evaporated and the catalyst was firmly attached to the electrode surface to obtain a working electrode.
[0088] When the electrolytic cell is used for electrochemical reduction of CO2, CO2 gas is introduced and the electric field strength of the electrolytic cell system is adjusted to 1.0×10 8 V / m for 10 min, and then electrochemically reduce CO2 at a potential of -1.0 V. The purity of CO2 gas is 99.999% and the flow rate is 15 cm 3 / min; in the electrochemical reduction of CO2, the reaction temperature is 20℃ and the reaction time is 100h.
[0089] Example 6: A method for electrochemical reduction of CO2 based on tip-enhanced electric field
[0090] A working electrode was prepared using a nano-triangular gold catalyst (AuNTs) rich in tip structures, Pt was used as a counter electrode, Ag / AgCl was used as a reference electrode, and 0.07M sulfuric acid was used as an electrolyte solution, which was loaded into a gas flow electrolytic cell to construct an electrolytic cell system for electrochemical reduction of CO2;
[0091] The specific preparation steps of the working electrode are:
[0092] (a) 410 μg of a nano-triangular gold catalyst (AuNTs) rich in tip structures was dispersed in 500 μL of a hexadecyltrimethylammonium bromide solution to obtain a nano-triangular gold catalyst solution; 80 μL of a 5 wt % Nafion solution was added to 2.5 mL of the nano-triangular gold catalyst solution as a binder to improve the adhesion of the catalyst on the electrode surface, and 3 mL of isopropanol was added to promote dispersion uniformity, and ultrasonic stirring was performed for 25 min to obtain a catalyst ink;
[0093] (b) A 10 cm × 10 cm gas diffusion electrode (GDE) was selected as the electrode substrate, which was washed alternately with deionized water and isopropanol three times, and then dried at 60 °C for later use;
[0094] Use a sprayer to spray the catalyst ink onto the surface of the electrode substrate. The spray volume is 12 μL each time. After evenly distributing the coating, dry it. Repeat the spraying 3–5 times until the loading amount of the catalyst ink on the electrode substrate reaches 0.6 mg / cm 2The coated electrode was then placed at room temperature to dry naturally for 35 minutes, and then placed at 55°C to dry for 1 hour to ensure that the solvent was completely volatilized and the catalyst was firmly attached to the electrode surface to obtain a working electrode.
[0095] When the electrolytic cell is used for electrochemical reduction of CO2, CO2 gas is introduced and the electric field strength of the electrolytic cell system is adjusted to 1.1×10 8 V / m for 20 min, and then electrochemically reduce CO2 at a potential of -1.0 V. The purity of CO2 gas is 99.999% and the flow rate is 25 cm 3 / min; in the electrochemical reduction of CO2, the reaction temperature is 28℃ and the reaction time is 100h.
[0096] Comparative Example 1: Preparation of Obtuse-Angled Gold Nanocatalyst (AuNPs)
[0097] (1) Add 0.125 mL of 0.01 M HAuCl4 solution to 3.75 mL of 0.1 M hexadecyltrimethylammonium bromide (CTAB) solution, mix well, then add 0.3 mL of 0.01 M ice-cold NaBH4 solution, quickly invert and mix for 2 min, and let stand at room temperature for 1 h to obtain a seed solution;
[0098] (2) adding 6.4 mL of 0.1 M hexadecyltrimethylammonium bromide (CTAB) solution, 0.8 mL of 0.01 M HAuCl4 solution and 3.8 mL of 0.1 M ascorbic acid solution to 32 mL of deionized water in sequence, and mixing well to obtain a growth solution;
[0099] (3) The seed solution prepared in step (1) is diluted 20 times and added to the growth solution prepared in step (2). The mixture is mixed by inversion for 10 seconds and then allowed to stand overnight. The mixture is separated and the precipitate is collected to obtain the obtuse-angle gold nanoparticles (AuNPs).
[0100] The obtuse-angled nano-gold catalyst (AuNPs) prepared in this comparative example has uniform size, a nearly spherical shape, and a side length of about 35.98±5.45 nm.
[0101] Test Example 1:
[0102] The nanotriangular gold catalyst (AuNTs) prepared in Example 1, the obtuse nanogold catalyst (AuNPs) prepared in Comparative Example 1, and the commercial gold-carbon catalyst (AuCPs) were respectively used to construct an electrolytic cell system that can be used for electrochemical reduction of CO2. CO2 gas was introduced into the above electrolytic cell system and treated at a potential of -1.0V for 30min. At the same potential, the three catalysts showed different electric field strengths. The dipole moment of the CO2 molecule and the C=O bond length were detected. The results are shown in Table 1.
[0103] Table 1 CO2 molecular dipole moment and C=O bond length
[0104]
[0105]
[0106] It can be seen from Table 1 that the nanotriangular gold catalyst (AuNTs) prepared in the present invention can form a tip electric field in a strong electric field. Compared with nanogold catalysts of other morphologies, a higher local electric field is generated at the tip, which enhances the dipole moment and C=O bond length of the CO2 molecule, and significantly enhances the polarization ability of the CO2 molecule.
[0107] Test Example 2: Electrochemical Performance
[0108] The triangular gold nanoparticles (AuNTs) prepared in Example 1, the obtuse gold nanoparticles (AuNPs) prepared in Comparative Example 1, and commercial gold-carbon catalysts (AuCPs) were used to prepare working electrodes to construct an electrolytic cell system for electrochemical reduction of CO2. The effective current density and Faraday efficiency (FE CO ) and cathode energy efficiency to reflect the electrochemical performance, the results are as follows Figure 5 shown.
[0109] The specific test steps are:
[0110] (1) The working electrodes are prepared from the nano-triangular gold catalyst (AuNTs) with a pointed structure prepared in Example 1, the obtuse nano-gold catalyst (AuNPs) prepared in Comparative Example 1, and the commercial gold-carbon catalyst (AuCPs), respectively. The preparation method of the working electrodes is the same as that of Example 4;
[0111] (2) Pt was used as a counter electrode, Ag / AgCl was used as a reference electrode, and 0.07 M sulfuric acid was used as an electrolyte solution, which were loaded into a gas flow electrolytic cell to construct an electrolytic cell system for electrochemical reduction of CO2. When the electrolytic cell was used for electrochemical reduction of CO2, CO2 gas was introduced and the electric field strength of the electrolytic cell system was adjusted to 1.2×10 8 V / m for 30 min, and then electrochemically reduce CO2 at a potential of -1.0 V. The purity of CO2 gas is 99.999% and the flow rate is 20 cm 3 / min; in the electrochemical reduction of CO2, the reaction temperature is 25℃ and the reaction time is 100h.
[0112] (3) Detect the effective current density (j CO ), Faraday efficiency (FE CO ), and cathode energy efficiency.
[0113] Among them, the total current density (j total ) detection steps are: apply a fixed working voltage and record the corresponding current (I 测量 ), and the total current density is calculated by formula (I).
[0114] j 总 =I 测量 / A 电极 Formula (I);
[0115] In the formula, j 总 is the total current density, I 测量 To measure the current, A 电极 is the effective area of the working electrode.
[0116] The detection steps of Faraday efficiency are as follows: connect the gas phase outlet of the electrolytic cell to a gas chromatograph (GC) to detect the gas phase product in real time; calculate the molar amount of CO generated n according to the CO signal peak area measured by GC through the standard gas calibration curve CO , and then use formula (II) to calculate the Faraday efficiency;
[0117] FE CO =[z×F×(n CO / Q total )] 100% formula (II);
[0118] In the formula, z is the number of electrons transferred (CO generation corresponds to 2 electrons), F is the Faraday constant, which is 96485C / mol, and n CO is the molar amount of CO produced, in mol, Q total is the total charge, in units of C, and its calculation formula is shown in formula (III), Q total =∫I(t)dt formula (III).
[0119] The calculation formula of effective current density is shown in formula (IV):
[0120] Effective current density (j CO ) = total current density (j 总 )×Faraday efficiency (FE CO )Formula (IV).
[0121] The cathode energy efficiency (CEE) is calculated by formula (V):
[0122]
[0123] In the formula, E CO is –0.109 V, which is the standard thermodynamic electrode potential of CO2 / CO (relative to RHE), FE CO is the Faradaic efficiency of CO production, E cathodeis the applied cathodic potential (relative to RHE).
[0124] Depend on Figure 5 It can be seen that under the same potential conditions (-1.0 V vs RHE), the effective current density (j CO ), the CO generation current density (j CO ) up to 122mA / cm 2 , while AuNPs and AuCPs were only 29.6 mA / cm 2 and 14.6mA / cm 2 ; Faraday efficiency (FE CO ), the Faraday efficiency (FE CO ) is 99%, while AuNPs and AuCPs are only 65.4% and 53.3% respectively; in terms of cathode energy efficiency (CEE), the cathode energy efficiency (CEE) of the nano-triangular gold catalyst AuNTs prepared by the present invention is 59%, while AuNPs and AuCPs are only 39% and 32% respectively. It can be seen that the tip-enhanced electric field formed by the nano-triangular gold catalyst AuNTs prepared by the present invention under the action of a strong electric field has a significant advantage in improving the activity of the CO2 reduction reaction.
[0125] Test Example 3: Stability Test
[0126] The electrolytic cell system prepared in Example 4 was used for electrochemical reduction of CO2. The electrolysis was continued for 100 h. The total current density (j total ) and Faraday efficiency (FE CO ) to reflect stability, the results are as follows Figure 6 shown.
[0127] Depend on Figure 6 It can be seen that during the 100-hour electrolysis process, the FE of the nano-triangular gold catalyst AuNTs prepared by the present invention is CO Almost remained above 97%, while the highest FE of AuNPs and AuCPs CO The AuNTs catalyst showed excellent energy efficiency in a wide potential range (-0.7V to -1.1V), with the highest reaching about 60%. It can be seen that the AuNTs prepared by the present invention showed excellent stability in a strong acid electrolyte, and could maintain a stable current density and selectivity during an electrolysis process of up to 100 hours, indicating that the catalyst has good durability and stability in practical applications.
[0128] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for electrochemical reduction of CO2 based on tip-enhanced electric field, characterized in that: The following steps are involved: The working electrode was prepared using nano-triangular gold catalysts, and sulfuric acid was used as the electrolyte solution to construct an electrolytic cell system for electrochemical reduction of CO2. The nano-triangular gold catalyst is prepared by the following method: (1) mixing a hexadecyltrimethylammonium bromide solution, a KI solution and a gold chloride solution to obtain a mixed solution; adding a NaOH solution and an ascorbic acid solution to the mixed solution in sequence, and waiting for the solution to become colorless to obtain a precursor solution; (2) adding NaOH solution to the precursor solution until the solution turns blue to obtain a nano-triangular gold catalyst dispersion; (3) adding hexadecyltrimethylammonium bromide solution to the nano-triangular gold catalyst dispersion, mixing and then standing, purifying and centrifuging, collecting the precipitate after centrifugation, and obtaining the nano-triangular gold catalyst.
2. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: When the electrolytic cell system is used for electrochemical reduction of CO2, CO2 gas is introduced and the electric field strength of the electrolytic cell system is adjusted to 1.0×10 8 -1.2×10 8 V / m treatment for 10-30 min, and then electrochemical reduction of CO2 was carried out at a potential of -0.7V to -1.1V.
3. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: The purity of CO2 gas is 99.999% and the flow rate is 15-25cm 3 / min; in the electrochemical reduction of CO2, the reaction temperature is 20-28°C and the reaction time is 100h.
4. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: In step (1), the volume ratio of hexadecyltrimethylammonium bromide solution, KI solution and gold chloride solution is (9.5-9.8) mL: (70-80) μL: 80 μL; the volume ratio of gold chloride solution, NaOH solution and ascorbic acid solution is 80: (20-21):
80.
5. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: In step (1), the concentration of the KI solution is 0.01M, the gold chloride solution is a mixture of HAuCl4·3H2O and water, the concentration of the gold chloride solution is 25.4mM, the concentration of the NaOH solution is 0.1M, and the concentration of the ascorbic acid solution is 0.064M.
6. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: In step (2), the volume ratio of the precursor solution to the NaOH solution is (3-5):
1.
7. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: In step (3), the volume ratio of the nano-triangular gold catalyst dispersion and the hexadecyltrimethylammonium bromide solution is 1:1; and the standing time is 24-40 hours.
8. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 1, characterized in that: The specific operation of preparing the working electrode using the nano-triangular gold catalyst rich in tip structure is as follows: (a) dispersing a nano-triangular gold catalyst rich in tip structures into a hexadecyltrimethylammonium bromide solution to obtain a nano-triangular gold catalyst solution; Then, Nafion solution and isopropanol were added to the nano-triangle gold catalyst solution, and the catalyst ink was obtained after stirring. (b) Spraying the catalyst ink onto the surface of the electrode substrate and drying it to obtain a working electrode.
9. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 8, characterized in that: In step (a), the volume ratio of the nano-triangle gold catalyst solution, the Nafion solution and the isopropanol is (1.5-2.5) mL: 80 μL: 3 mL; the concentration of the Nafion solution is 5 wt %.
10. The method for electrochemical reduction of CO2 based on tip-enhanced electric field according to claim 8, characterized in that: In step (b), the loading amount of the catalyst ink on the electrode substrate is 0.4-0.6 mg / cm 2 .